Mechanisms of vitamin D action in skeletal muscle - Montenegro, Karina Romeu; Cruzat, Vinicius; Carlessi, Rodrigo; Newsholme, Philip (Nutrition research reviews, 2019)
Vitamin D receptor expression and associated function have been reported in various muscle models, including C 2 C 12 , L6 cell lines and primary human skeletal muscle cells. It is believed that 1,25-hydroxyvitamin D 3 (1,25(OH) 2 D 3 ), the active form of vitamin D, has a direct regulatory role in skeletal muscle function, where it participates in myogenesis, cell proliferation, differentiation, regulation of protein synthesis and mitochondrial metabolism through activation of various cellular signalling cascades, including the mitogen-activated protein kinase pathway(s). It has also been suggested that 1,25(OH) 2 D 3 and its associated receptor have genomic targets, resulting in regulation of gene expression, as well as non-genomic functions that can alter cellular behaviour through binding and modification of targets not directly associated with transcriptional regulation. The molecular mechanisms of vitamin D signalling, however, have not been fully clarified. Vitamin D inadequacy or deficiency is associated with muscle fibre atrophy, increased risk of chronic musculoskeletal pain, sarcopenia and associated falls, and may also decrease RMR. The main purpose of the present review is to describe the molecular role of vitamin D in skeletal muscle tissue function and metabolism, specifically in relation to proliferation, differentiation and protein synthesis processes. In addition, the present review also includes discussion of possible genomic and non-genomic pathways of vitamin D action.